Optimisation of inductive telemetry links in an implantable medical device for a wireless range of 25 cm. Issue 23 (1st November 2018) - John, B.; Spink, C.; Braunschweig, M.; Ranjan, R.; Schroeder, D.; Koops, A.; Woldt, G.; Adam, G.; Krautschneider, W.H.
Abstract : The optimisation of inductive telemetry link for increasing wireless range of a medical implant device is studied in detail. An active implant device using separate wireless power and data links at 2 MHz and 420 kHz has been fabricated and tested. A test setup consisting of RF power transmitter and data reader hardware has been implemented. Measurement results show that the fabricated device achieved a wireless range of 25 cm.